Multilingua : Journal of Cross-Cultural and Interlanguage Communication (De Gruyter Mouton, 1982)
Multilingua is a refereed academic journal devoted to multilingualism, language learning, intercultural communication and translating and interpreting in their social contexts. Multilingua focuses on critical sociolinguistic studies of language and communication in globalization, transnationalism, migration and mobility across time and space. It is an international forum for interdisciplinary research on linguistic diversity in social life.